An unusual association of hadrosaur and therizinosaur tracks within Late Cretaceous rocks of Denali National Park, Alaska - Anthony R. Fiorillo (Nature Portfolio, 2018)
Abstract We report details of a unique association of hadrosaur and therizinosaur tracks found in the Late Cretaceous lower Cantwell Formation, Denali National Park, central Alaska Range, Alaska. This rock unit is now well-documented as a source of thousands of fossil footprints of vertebrates such as fishes, pterosaurs, and avialan and non-avialan dinosaurs. The lower Cantwell Formation in this area consists of numerous fining-upward successions of conglomerates and pebbly sandstones, cross-stratified and massive sandstones, interbedded sandstones and siltstones, organic-rich siltstones and shales, and rare, thin, bentonites, typically bounded by thin coal seams, and it contains a diverse fossil flora. We report the first North American co-occurrence of tracks attributable to hadrosaurs and therizinosaurs in the lower Cantwell Formation. Although previously un-reported in North America, this association of hadrosaur and therizinosaur tracks is more characteristic of the correlative Nemegt Formation in central Asia, perhaps suggesting that parameters defining the continental ecosystem of central Asia were also present in this part of Alaska during the Latest Cretaceous.